Characterization of Right Ventricular Remodeling in Pulmonary Hypertension Associated With Patient Outcomes by 3-Dimensional Wall Motion Tracking Echocardiography. (June 2015) - Ryo, Keiko; Goda, Akiko; Onishi, Tetsuari; Delgado-Montero, Antonia; Tayal, Bhupendar; Champion, Hunter C.; Simon, Marc A.; Mathier, Michael A.; Gladwin, Mark T.; Gorcsan, John
Abstract : Background—: Adverse right ventricular (RV) remodeling has significant prognostic and therapeutic implications to patients with pulmonary hypertension (PH). However, differentiating RV adaption from adverse remodeling associated with poor outcomes is difficult. We hypothesized that novel 3-dimensional (3D) wall motion tracking echocardiography can differentiate morphological features of RV adaption from adverse remodeling heralding an unfavorable short-term prognosis in patients with PH. Methods and Results—: We studied 112 subjects: 92 patients with PH and 20 normal controls with 3D wall motion tracking for RV end-systolic volume index (ESVi), RV ejection fraction (EF), and RV global area strain. Patients with PH also had invasive hemodynamic measurements. Pressure–volume relations classified patients with PH into 3 groups, such as RV adapted, RV adapted–remodeled, and RV adverse–remodeled. The predefined combined end point was PH-related hospitalization, death, or lung surgery (lung transplantation or pulmonary endarterectomy) during 6 months. The 92 patients with PH had significantly larger RV volumes, lower RVEF and global area strain than normal controls as expected. Patients with PH classified as RV adapted (ESVi, ⩽ 72 mL/m 2 ) had a more favorable clinical outcome than those classified as RV adapted–remodeled (ESVi, 73–113 mL/m 2 ) or RV adverse–remodeled (ESVi, ≥ 114 mL/m 2 ): hazard ratio, 0.15; 95% confidence intervals, 0.07 to 0.39; P <0.0001. RV adverse–remodeled patients (ESVi, ≥ 114 mL/m 2 ) had worse short-term outcome than the RV adapted–remodeled patients: hazard ratio, 2.2; 95% confidence interval, 0.91 to 5.39; P =0.04. Conclusions—: Quantitative 3D echocardiography in patients with PH demonstrated morphological subsets of RV adaption and remodeling associated with clinical outcomes.